Enhancing Performance Through Digital Competence: The Mediating Role of Engagement and Communication Among Civil Servants - Maizon, Hepi; Ahman, Eeng; Yuniarsih, Tjutju; Santoso, Budi (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The rapid advancement of digital technology demands strong digital competence, particularly among civil servants in educational institutions. This study aims to examine the influence of digital competence on civil servants’ performance, investigating both direct effects and indirect pathways through employee engagement and interpersonal communication. Methodology: A quantitative survey method was employed involving 150 civil servants working in public educational institutions in Riau, Indonesia. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Main Findings: The results indicate that digital competence has a significant positive impact on performance, both directly and indirectly. Employee engagement and interpersonal communication serve as effective mediators that enhance the relationship between digital competence and performance. The findings suggest that civil servants who possess strong digital skills, coupled with high engagement and effective interpersonal communication, demonstrate better job performance. Novelty/Originality of this study: This study offers a novel contribution by integrating psychological (employee engagement) and relational (interpersonal communication) dimensions as mediators in the relationship between digital competence and performance. While previous studies have focused mainly on technological aspects, this research highlights the importance of human and social factors in driving performance in digitally transforming institutions. The implication of these findings points to the need for a more holistic approach to digital transformation policies in the public sector, where capacity building should not only address technical skills but also foster engagement and communication abilities among employees.